Latent Infection of Powdery Mildew on Volunteer Wheat in Sichuan Province, China - Liu, Na (Plant disease, 2019)
Wheat powdery mildew, caused by the fungal pathogen Blumeria graminis f. sp. tritici, is one of the most destructive wheat diseases in China, especially in Sichuan Province. Successfully oversummered B. graminis f. sp. tritici can become a primary infection source for wheat seedlings in the fall. Determining the latent infection level of B. graminis f. sp. tritici in volunteer wheat and the oversummering areas of B. graminis f. sp. tritici is important for estimating potential B. graminis f. sp. tritici epidemics. In this study, we clarified the critical role of volunteer wheat in the B. graminis f. sp. tritici oversummering cycle and determined whether latent B. graminis f. sp. tritici infection was present in volunteer wheat by using real-time polymerase chain reaction (real-time PCR). The results indicated that volunteer wheat was mostly found in the northeast and middle regions of Sichuan, where lower temperatures and higher precipitation are common. A total of 13.2% of samples showed symptoms of B. graminis f. sp. tritici (spores) in the field, and 36.8% of samples were found to carry the B. graminis f. sp. tritici pathogen, even though no symptoms were observed. Volunteer wheat with B. graminis f. sp. tritici infection symptoms was found at an altitude of 536 m but volunteer wheat latently infected by B. graminis f. sp. tritici was identified at the lowest altitude of 323 m. Crop shade (e.g., corn and lima bean) provided suitable conditions for the survival of volunteer wheat in the summer. In addition, volunteer wheat played a key role in the B. graminis f. sp. tritici oversummering cycle. Moreover, B. graminis f. sp. tritici could oversummer by infecting generations of volunteer wheat in the summer, thereby becoming the primary infection source for autumn-sown wheat. The results showed that the latent infection of wheat diseases could be rapidly quantified by real-time PCR. Here, the primary disease center of autumn-sown wheat in Ya'an and Wenjiang were detected accurately based on this method. This study provides solid evidence for identifying the disease center, which offers guidance for wheat disease control and management